2020
DOI: 10.1177/1354816620939722
|View full text |Cite
|
Sign up to set email alerts
|

Marketing, congestion, and demarketing in Utah’s National Parks

Abstract: Utah’s Mighty 5 ad campaign was designed to attract out-of-state visitors to southern Utah’s five National Parks (NPs). Using the synthetic control method, we find the campaign to have contributed to rapid visitation growth at Arches, Canyonlands, and Capitol Reef NPs. No ad campaign effect was found for Bryce Canyon and Zion NPs, which implies that recent increased visitation at these parks has been driven by the national trends and not the Mighty 5 promotion. Arches, Bryce Canyon, and Zion currently suffer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The effort has been successful, attracting on average an additional half-million visitors per year to Utah's national parks (Maffly, 2019). While a variety of factors have contributed to increasing visitation to national parks, in Utah and nationally, Utah State University researchers found that the Mighty Five advertising expanded visitation growth exponentially for Arches, Canyonlands and Capitol Reef National Parks (Drugova et al , 2020). From 2010 to 2019, visitation to Utah's “Mighty Five” national parks increased nearly 70% overall (59.47% at Arches, 100.22% at Bryce Canyon, 54.93% at Canyonlands, 83.38% at Capitol Reef and 58.85% at Zion) (Department of the Interior, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effort has been successful, attracting on average an additional half-million visitors per year to Utah's national parks (Maffly, 2019). While a variety of factors have contributed to increasing visitation to national parks, in Utah and nationally, Utah State University researchers found that the Mighty Five advertising expanded visitation growth exponentially for Arches, Canyonlands and Capitol Reef National Parks (Drugova et al , 2020). From 2010 to 2019, visitation to Utah's “Mighty Five” national parks increased nearly 70% overall (59.47% at Arches, 100.22% at Bryce Canyon, 54.93% at Canyonlands, 83.38% at Capitol Reef and 58.85% at Zion) (Department of the Interior, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work has historically been site focused [58,64], with national parks and heritage sites receiving substantial emphasis [59,63,81,82]. Such a situation perhaps reflects Drugova et al's observation that the "overcrowding of nature tourism sites has been documented on every continent" [65] (p. 2) Nevertheless, in recent years there has been a much stronger focus on demarketing urban places and locations [62,83], especially in response to the pressures of overtourism [2,84,85], to the stage where they have become the major institutional focus for overtourism [86,87].…”
Section: What Is Being Demarketed?mentioning
confidence: 97%
“…However, as the concept developed it was increasingly adopted to help manage environmental issues by modifying and/or reducing consumer demand [56,57]. As a result, demarketing gradually became of interest to tourism researchers who were seeking ways by which to limit the environmental impacts of tourism [58][59][60][61][62][63], particularly since the emergence of overtourism as a high-profile research concern [64][65][66].…”
Section: Demarketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Demarketing strategies create opportunities to use visitor management tools in the marketing stage (Beeton, 2006). Many studies such as , Beeton (2002), Beeton and Benfield (2002), Wearing, Archer and Beeton (2007), Medway and Warnaby (2008), Medway, Warnaby and Dharni (2010), Sadiki (2012), Nared and Visković (2014), Magalhães et al (2017), Eliasson and Velasco (2018), Weiler et al (2018), Kumar and Srivastav (2019), Olokesusi et al (2019), Drugova, Kim and Jakus (2020) emphasized using demarketing strategies to manage tourist demands.…”
Section: Uvodmentioning
confidence: 99%